Positive electrode sheet for air battery and air battery using same

The use of a fibrous carbon positive electrode sheet with tailored pore volume and surface area addresses the limitations of existing carbon nanotube-based sheets, enhancing discharge rates and cycle durability in air batteries.

JP7648126B2Active Publication Date: 2025-03-18NAT INST FOR MATERIALS SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020203242
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-08
Publication Date
2025-03-18
Estimated Expiration
2040-12-08

AI Technical Summary

Technical Problem

Existing positive electrode sheets for air batteries, particularly those made of carbon nanotubes, exhibit insufficient discharge characteristics at high speeds and limited cycle life.

Method used

A positive electrode sheet for air batteries made of fibrous carbon with a specific pore volume of 2.0 to 10.0 cm³/g for pores with diameters of 0.1 to 10 μm and a specific surface area of 400-1300 m²/g, as determined by the BET method, is developed. This design enhances diffusion and affinity with the electrolyte.

Benefits of technology

The fibrous carbon positive electrode sheet achieves excellent discharge characteristics at high speeds and improved cycle life, enabling efficient oxygen diffusion and ion transport within the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648126000006
    Figure 0007648126000006
  • Figure 0007648126000007
    Figure 0007648126000007
  • Figure 0007648126000008
    Figure 0007648126000008
Patent Text Reader

Abstract

To provide a positive electrode sheet for an air cell capable of presenting excellent discharge characteristics at high speed, and an air cell using the same.SOLUTION: A positive electrode sheet for an air cell consists of fibrous carbons. In the sheet, a pore volume of a pore with a diameter of 0.1 to 10 μm ranges from 2.0 to 10.0 cm3 / g, and a BET method specific surface area ranges from 400 to 1300 m2 / g. An apparent density of the sheet may also range from 0.05 to 0.2 g / cm3. The fibrous carbons may also be selected from among a carbon nano-tube, carbon nanohorn and a carbon nanofiber.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode sheet for an air battery and an air battery using the same, and more particularly to a positive electrode sheet for an air battery using fibrous carbon and an air battery using the same. [Background technology]

[0002] In recent years, the spread of renewable energy and the demand for electrified vehicles have necessitated the development of lightweight, large-capacity storage batteries, i.e., batteries with higher energy density. Among the secondary batteries that can be envisioned for realization, the lithium-air battery has the highest theoretical energy density, and can achieve an energy density that far exceeds that of the currently popular lithium-ion batteries.

[0003] Lithium-air batteries use lithium metal as the negative electrode active material and atmospheric oxygen as the positive electrode active material. During discharge, the lithium metal negative electrode dissolves (Li⇔Li + +e - ), which reacts with oxygen absorbed from the air at the positive electrode to precipitate lithium peroxide (2Li + +2e - +O2⇔Li2O2). When charging, the reverse reaction occurs, and these reactions are repeated to charge and discharge the battery. The positive electrode is also called the air electrode, since it absorbs and releases atmospheric oxygen during charging and discharging.

[0004] A sheet-shaped electrode made of carbon nanotubes has been developed as such a positive electrode (see, for example, Non-Patent Document 1). Non-Patent Document 1 reports that a free-standing carbon nanotube sheet can be obtained by vacuum filtering a slurry in which single-walled carbon nanotubes are dispersed in isopropanol through a polytetrafluoroethylene (PTFE) filter. By using such a carbon nanotube sheet as the positive electrode of an air battery, the cell capacity has been dramatically improved. However, the high-speed discharge characteristics (discharge capacity when current is extracted at a higher current density by increasing the output rate) are insufficient. In addition, the cycle characteristics also have a limit to the number of times that the battery can be charged and discharged.

[0005] On the other hand, a free-standing film using carbon nanotubes is known (see, for example, Patent Document 1). Patent Document 1 discloses that a free-standing film is obtained by filtering a dispersion liquid containing carbon nanotubes produced by the super-growth method and surface-treated with peroxide. Such a free-standing film has electrical conductivity and is applied to electronic devices and electronic components such as touch panels, solar cells, and fuel cells, but has not been considered for use as a positive electrode for air batteries. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2015-105208 A [Non-patent literature]

[0007] [Non-Patent Document 1] Akihiro Nomura et al.,Scientific Reports 7, Article number:45596,2017 Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above, an object of the present invention is to provide a positive electrode sheet for an air battery capable of exhibiting excellent high-rate discharge characteristics, and an air battery using the same. [Means for solving the problem]

[0009] The positive electrode sheet for an air battery of the present invention is made of fibrous carbon, and the pore volume of the pores having a diameter of 0.1 to 10 μm is 2.0 to 10.0 cm 3 / g, and the BET specific surface area is 400 to 1300 m 2 / g range, thereby solving the above problem. Apparent density: 0.05 to 0.2 g / cm 3 may satisfy the range. The apparent density is 0.07 to 0.19 g / cm 3 may satisfy the range. The pore volume of the pores having a diameter of 0.1 to 10 μm is 2.3 to 8.0 cm 3 / g range may be satisfied. The pore volume of the pores having a diameter of 0.1 to 10 μm is 2.5 to 5.0 cm 3 / g range may be satisfied. The BET specific surface area is 500 to 1200 m 2 / g range may be satisfied. The BET specific surface area is 550 to 1000 m 2 / g range may be satisfied. The fibrous carbon may be selected from the group consisting of carbon nanotubes, carbon nanohorns, and carbon nanofibers. A portion of the fibrous carbon may be in the form of a bundle. The intensity ratio D / G of the peak intensity D originating from turbostratic carbon to the peak intensity G originating from crystalline carbon obtained by Raman spectroscopy may be within the range of 0.1 to 1.0. The intensity ratio D / G may be in the range of 0.2 to 0.8. The pore volume of pores with diameters of 2 to 1000 nm is 0.5 to 2.0 cm 3 / g range may be satisfied. The pore volume of the pores having a diameter of 2 to 1000 nm is 0.7 to 1.0 cm 3 / g range may be satisfied. The porosity of the positive electrode sheet may be in the range of 80 to 95%. The electrolyte permeation time when a 10 μL droplet is permeated into the positive electrode sheet may be in the range of more than 0 minutes to 6 minutes. The electrolyte permeation time may be in the range of more than 0 minutes and not more than 2 minutes. The positive electrode sheet may have a thickness in the range of 50 to 400 μm. The weight of the positive electrode sheet is 2 to 3.5 mg / cm 2 may satisfy the range. The air battery of the present invention comprises a positive electrode, a negative electrode, and an electrolyte capable of conducting metal ions between the positive electrode and the negative electrode, and the positive electrode comprises the above-mentioned positive electrode sheet, thereby solving the above-mentioned problems. The negative electrode may comprise a lithium metal layer and the metal ions may be lithium ions. Effect of the Invention

[0010] The positive electrode sheet for an air battery of the present invention is made of fibrous carbon, and the pore volume of the pores having a diameter of 0.1 to 10 μm is 2.0 to 10.0 cm 3 / g, and the BET specific surface area is 400 to 1300 m 2 By adjusting the composition so as to satisfy these specific conditions, oxygen and metal ions such as lithium ions are sufficiently diffused and the affinity with the electrolyte is increased, so that an air battery having excellent high-speed discharge characteristics and excellent cycle characteristics can be provided. [Brief description of the drawings]

[0011] [Figure 1] A flowchart showing the steps of manufacturing the positive electrode sheet for an air battery of the present invention. [Diagram 2] Schematic cross-sectional view of an air battery according to an embodiment of the present invention. [Diagram 3]FIG. 1 is a schematic cross-sectional view of an air battery, which is a laminated metal battery, which is another embodiment of the air battery of the present invention. [Figure 4] FIG. 1 shows an SEM image of the sheet of Example 1. [Diagram 5] FIG. 1 shows an SEM image of the sheet of Example 3. [Figure 6] FIG. 1 shows an SEM image of the sheet of Example 5. [Figure 7] FIG. 1 shows an SEM image of the sheet of Example 6. [Figure 8] FIG. 1 shows an SEM image of the sheet of Example 7. [Figure 9] FIG. 1 shows an SEM image of the sheet of Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that like elements are given like reference numerals and their description will be omitted. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0013] (Embodiment 1) In the first embodiment, a positive electrode sheet for an air battery and a method for producing the same of the present invention will be described.

[0014] To improve the output and capacity of an air battery cell (e.g., a lithium-air battery), the air electrode, which is the positive electrode, must have sufficient conductivity as an electrode, and at the same time, it must have an electrochemically active surface where the battery reaction occurs, and it must have a diffusion path that can supply the battery reactants oxygen and lithium ions to the electrochemically active surface. This diffusion path also serves to provide a space for the accumulation of a large amount of solid products (mainly lithium peroxide (Li2O2)) that are precipitated by the discharge reaction without inhibiting their growth. In other words, the positive electrode must have a continuous pore structure within the electrode that allows easy diffusion of substances, as well as a large pore volume and surface area.

[0015] From this viewpoint, the inventors of the present application have attempted to prepare a self-supporting sheet using fibrous carbon and control its pore volume and surface area for use in the positive electrode of an air battery. In the following, the case where the positive electrode sheet is used in a lithium-air battery will be mainly described, but the air battery includes not only lithium-air batteries but also air batteries that exchange external gases, such as sodium-air batteries, air zinc batteries, air iron batteries, air aluminum batteries, and air magnesium batteries.

[0016] [Positive electrode sheet for air batteries] The positive electrode sheet for an air battery of the present invention (hereinafter simply referred to as a positive electrode sheet) is made of fibrous carbon, and the pore volume of the pores having a diameter of 0.1 to 10 μm is 2.0 to 10.0 cm 3 / g, and the BET specific surface area is 400 to 1300 m 2 / g. It was found that by having such a specific pore volume and BET specific surface area, it is possible to provide an air battery that has excellent high-speed discharge characteristics (rate characteristics) and excellent cycle characteristics while maintaining a free-standing sheet.

[0017] The thickness of the positive electrode sheet is not limited, but is preferably in the range of 50 to 400 μm. This allows the sheet to function as a positive electrode of an air battery. From the viewpoints of miniaturization of the air battery and excellent discharge characteristics and cycle characteristics, the sheet more preferably has a thickness in the range of 100 to 200 μm.

[0018] (fibrous carbon) In the present specification, the fibrous carbon refers to carbon composed of layered carbon bonded by sp2 hybrid orbitals and having a fibrous form with an average diameter of 0.1 to 50 nm and an average length of about 1 to 100 μm. The average diameter is generally preferably 0.1 to 50 nm, and the average length is preferably 1 to 100 μm. The average aspect ratio (average of the length to the diameter of the fibrous carbon; length / diameter) is generally preferably 100 or more, more preferably 500 or more. There is no particular upper limit, but it is preferably 100,000 or less. In general, the smaller the diameter and the higher the aspect ratio of the fibrous carbon, the stronger the cohesive force acts on them, and the fibrous carbon is more likely to form a nonwoven fabric-like aggregate in which the fibrous carbon is linked in thick bundles of about 0.1 to 10 μm, as described below.

[0019] In this specification, the average aspect ratio means a value calculated as fiber length / fiber diameter from the fiber lengths and fiber diameters of 100 fibrous carbon fibers observed with a scanning electron microscope.

[0020] The fibrous carbon is preferably selected from the group consisting of carbon nanotubes, carbon nanohorns, and carbon nanofibers. All of these fibrous carbons are available. Among them, carbon nanotubes are preferred because they are cylindrical and can easily achieve the above-mentioned pore volume and specific surface area.

[0021] When carbon nanotubes are used as the fibrous carbon, the lower limit of the average aspect ratio is preferably at least 2000, more preferably at least 2500, and even more preferably at least 3000. When the average aspect ratio of the carbon nanotubes is at least the lower limit, the carbon nanotubes become more strongly entangled with each other, and a positive electrode sheet having excellent strength can be obtained.

[0022] The upper limit of the average aspect ratio of the carbon nanotubes is preferably not more than 100000, more preferably not more than 50000. When the average aspect ratio is not more than the upper limit, the carbon nanotubes have better dispersibility, and the positive electrode sheet can be produced with a good yield.

[0023] The carbon nanotube is not particularly limited, and may be a single-walled carbon nanotube (SWNT) or a multi-walled carbon nanotube (MWNT). In this specification, double-walled carbon nanotubes (DWNT) are included in the multi-walled carbon nanotube. Among them, SWNT is preferable as the carbon nanotube because it has better battery properties when applied to the positive electrode of a lithium-air battery.

[0024] A part of the fibrous carbon may be in a bundle shape. This increases the strength and allows the sheet to become self-supporting, making it easier to achieve the above-mentioned pore volume. In this case, the width of the bundle is preferably in the range of 0.1 μm to 10 μm.

[0025] (BET method specific surface area) The BET (Brunauer Emett Teller) specific surface area of ​​the positive electrode sheet of the present invention is 400 to 1300 m 2 / g. BET specific surface area is 400m 2 If the specific surface area is less than 1300 m / g, the efficiency of ion transport decreases, and when lithium ions react with oxygen to generate lithium peroxide, the reaction field required for oxygen to receive electrons supplied from the positive electrode decreases, which may result in a small discharge capacity. 2 If the specific surface area exceeds 1 / g, the contribution of side reactions on the positive electrode surface increases, making it difficult to obtain desirable charge / discharge characteristics. Note that the BET specific surface area is calculated by rounding off the first decimal place.

[0026] The lower and upper limits of the BET specific surface area are preferably 500 m 2 / g or more, more preferably 550m 2 / g or more, preferably 1200m 2 / g or less, more preferably 1000m2 / g or less. This allows the positive electrode sheet to have excellent discharge characteristics and strength. The range of the BET specific surface area may be set arbitrarily within the above-mentioned lower and upper limits, but the BET specific surface area of ​​the positive electrode sheet is, for example, 500 to 1200 m 2 / g, 550-1000m 2 / g range may be satisfied.

[0027] (Pore volume of pores with diameters of 0.1 to 10 μm) The pore volume of the pores having a diameter of 0.1 to 10 μm in the positive electrode sheet of the present invention is 2.0 to 10.0 cm 3 / g. The pore volume of pores with diameters of 0.1 to 10 μm is obtained using a value measured by mercury intrusion porosimetry. The BET specific surface area is calculated by rounding off to one decimal place.

[0028] The pores in this region mainly function to allow oxygen from outside the battery to penetrate into the positive electrode sheet. By satisfying the above-mentioned range of pore volume in this region, a sufficient amount of oxygen can penetrate at a high speed when lithium ions react with oxygen to generate lithium peroxide. As a result, by using the positive electrode sheet of the present invention, a battery having a large discharge capacity at a high current density, i.e., excellent high-speed discharge characteristics, can be provided.

[0029] During charging, lithium peroxide transfers electrons to the electrode to become Li ions and oxygen. By having the volume of pores with diameters of 0.1 to 10 μm or less fall within this range, the generated oxygen can easily escape from the positive electrode sheet, enabling high-speed charging.

[0030] The lower and upper limits of the pore volume of pores having a diameter of 0.1 to 10 μm are preferably 2.3 cm or less, so that the positive electrode sheet can exhibit the effects of the present invention. 3 / g or more, more preferably 2.5 cm 3 / g or more, preferably 8.0 cm 3 / g or less, more preferably 5.0 cm 3 / g or less. This allows the positive electrode sheet to have excellent discharge characteristics and strength. The range of the pore volume of pores having a diameter of 0.1 to 10 μm may be set arbitrarily to the above lower and upper limits, but the pore volume of pores having a diameter of 0.1 to 10 μm in the positive electrode sheet is, for example, 2.3 to 8.0 m 3 / g, 2.5-5.0m 3 / g range may be satisfied.

[0031] (Pore volume of pores with diameters of 2 to 1000 nm) The pore volume of the pores having a diameter of 2 to 1000 nm in the positive electrode sheet for an air battery of the present invention is preferably 0.5 to 2.0 cm 3 The pore volume of pores with a diameter of 2 to 1000 nm is obtained by the BJH (Barrett-Joyner-Hallenda) method from the adsorption isotherm obtained by nitrogen adsorption measurement. The value is rounded off to one decimal place.

[0032] The positive electrode sheet of the present invention has the above-mentioned pore volume, which increases the reaction sites for lithium peroxide to transfer electrons to the positive electrode and become lithium ions and oxygen during the charging reaction, thereby enabling the transfer of more electrons, thereby providing a battery with better discharge characteristics.

[0033] The lower and upper limits of the pore volume of pores having a diameter of 2 to 1000 nm are preferably 0.6 cm or less, so that the positive electrode sheet can exhibit the effects of the present invention. 3 / g or more, more preferably 0.7 cm 3 / g or more, more preferably 1.5 cm 3 / g or less, more preferably 1.0 cm 3 / g. This allows the positive electrode sheet to have excellent discharge characteristics while maintaining its strength. The range of the pore volume of the pores having a diameter of 2 to 1000 nm may be set arbitrarily to the above lower and upper limits, but the pore volume of the pores having a diameter of 2 to 1000 nm in the positive electrode sheet is, for example, 0.6 to 1.0 m 3 / g or less, 0.7-1.0m 3 / g or less

[0034] (D / G) The intensity ratio D / G of the peak intensity D derived from turbostratic carbon to the peak intensity G derived from crystalline carbon obtained by Raman spectroscopy of the positive electrode sheet of the present invention is preferably in the range of 0.1 to 1.0. Since the crystallinity is relatively low, the affinity between the sheet and the electrolyte is increased, resulting in a positive electrode sheet with excellent cycle characteristics. Note that D / G is calculated by rounding off to one decimal place.

[0035] The lower and upper limits of D / G are preferably 0.2 or more, more preferably 0.3 or more, and more preferably 0.8 or less, and even more preferably 0.6 or less, so that the positive electrode sheet can achieve the effects of the present invention. The range of D / G may be set arbitrarily with respect to the above lower and upper limits, but the D / G of the positive electrode sheet may be within the range of 0.2 to 0.8 or 0.3 to 0.6, for example.

[0036] (Apparent density) The apparent density (also referred to as sheet density) of the positive electrode sheet of the present invention is preferably 0.05 to 0.2 g / cm 3 This makes it possible to provide a positive electrode sheet having sufficient pores necessary for oxygen to permeate and diffuse and having excellent strength.

[0037] The lower and upper limits of the sheet density are preferably 0.07 g / cm3, respectively, in order for the positive electrode sheet to exhibit the effects of the present invention. 3 More preferably, 0.1 g / cm 3 More preferably, it is 0.19 g / cm 3 or less, more preferably 0.18 g / cm 3 The range of the sheet density is not limited as long as it is within the range of the above lower and upper limits, but the apparent density of the positive electrode sheet is, for example, 0.07 to 0.19 g / cm. 3 , 0.1~0.18g / cm 3 may satisfy the range.

[0038] (porosity) The porosity of the positive electrode sheet of the present invention is preferably in the range of 80 to 95%, which allows the positive electrode sheet to store a large amount of lithium peroxide produced during discharge and allows air and oxygen to enter the positive electrode from the outside of the battery without resistance, thereby providing a battery that has a high discharge capacity and is capable of high-speed discharge.

[0039] Here, the porosity is calculated from the apparent density and true density of the positive electrode sheet by the following formula: [1-(apparent density of positive electrode sheet / true density of material constituting the positive electrode sheet)]×100.

[0040] The lower and upper limits of the porosity are more preferably 83% or more, and even more preferably 85% or more, and more preferably 93% or less, and even more preferably 90% or less, in terms of enabling the positive electrode sheet to achieve the effects of the present invention.

[0041] (Electrolyte penetration time) The electrolyte permeation time when 10 μL of the droplet of the positive electrode sheet of the present invention is permeated into the positive electrode sheet is preferably in the range of more than 0 minutes to 6 minutes or less. This results in a positive electrode sheet with excellent affinity with the electrolyte, and therefore an air battery with excellent high-speed discharge characteristics and cycle characteristics can be provided.

[0042] The electrolyte penetration time is the time from when a 10 μL droplet (standard solution) is dropped onto the top surface of the target positive electrode sheet until the entire droplet completely penetrates and disappears from the top surface. In this specification, the electrolyte penetration time is defined as the time from when a 2 cm2 droplet is dropped onto the top surface of the target positive electrode sheet until the entire droplet completely penetrates and disappears from the top surface. 2 It is the time from when 10 μL of an electrolyte with a viscosity in the range of 8 to 13 mPa·S at 20°C is dropped onto a positive electrode sheet with a thickness in the range of 50 to 150 μm at 20°C until it disappears from the top surface. One such electrolyte is a 1M tetraethylene glycol dimethyl ether solution of LiTFS (lithium trifluoromethanesulfonate).

[0043] The upper limit of the electrolyte permeation time is more preferably 2 minutes or less, and even more preferably 1 minute or less, in terms of enabling the positive electrode sheet to exhibit the effects of the present invention.

[0044] (Met) The basis weight of the positive electrode sheet of the present invention is preferably 2 to 3.5 mg / cm 2 This satisfies the range. As a result, the positive electrode sheet has a high discharge capacity and can provide a battery that can discharge at a high speed. The weight per area was determined by punching out the target positive electrode sheet to a diameter (φ) of 16 mm, measuring its weight (mg).

[0045] [Method of manufacturing positive electrode sheet for air battery] Next, a method for producing the above-mentioned air battery positive electrode sheet will be described. FIG. 1 is a flow chart showing the steps of producing the air battery positive electrode sheet of the present invention.

[0046] Step S110: The fibrous carbon is dispersed in a dispersion medium to obtain a dispersion liquid of the fibrous carbon. The fibrous carbon here also has layered carbon bonded mainly by sp2 hybrid orbitals, and the above-mentioned fibrous carbon can be used. The fibrous carbon as a raw material is 400 to 1300 m. 2 / g and 8.0 to 15.0 cm 3 The pore volume of the pores having a diameter of 2 to 1000 nm satisfies the range of 1 / g. When the BET specific surface area of ​​the raw material fibrous carbon satisfies the above range, a reaction field is maintained and a self-supporting positive electrode sheet is obtained. When the pore volume of the raw material fibrous carbon satisfies the above range, the reaction field in the charging reaction increases, and a battery having excellent discharge characteristics can be provided.

[0047] The lower and upper limits of the BET specific surface area of ​​the fibrous carbon as the raw material are preferably 800 m2 or less, so that the positive electrode sheet can exhibit the effects of the present invention. 2 / g or more, more preferably 1000m 2 / g or more, preferably 1280m 2 / g or less, more preferably 1250m 2 / g or less.

[0048] The lower and upper limits of the pore volume of the pores having a diameter of 2 to 1000 nm in the fibrous carbon as the raw material are preferably 8.5 cm3 or less, so that the positive electrode sheet can exhibit the effects of the present invention. 3 / g or more, more preferably 9.0m 2 / g or more, preferably 12.0m 2 / g or less, more preferably 11.5m 2 / g or less.

[0049] The above-mentioned fibrous carbon is preferably a single-walled carbon nanotube.

[0050] As the dispersion medium, water and commonly available organic solvents can be used. Examples of organic solvents include, but are not limited to, N-methyl-2-pyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide, as well as various alcohols (e.g., methanol, ethanol, isopropanol), ethers, esters, carbonates, aromatic hydrocarbon solvents, and hydrocarbon solvents. The solvent can be selected in consideration of the characteristics (average length, average outer diameter, dispersibility, etc.) of the fibrous carbon used. The solvent may be a single solvent or a mixed solvent.

[0051] The lower and upper limits of the concentration of the fibrous carbon in the dispersion are preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and preferably 0.5% by mass or less, more preferably 0.3% by mass or less. The concentration of the fibrous carbon in the dispersion is preferably in the range of 0.01 to 0.3% by mass, more preferably 0.01 to 0.1% by mass. This allows the above-mentioned positive electrode sheet to be obtained with good yield.

[0052] Furthermore, a dispersion of fibrous carbon can be obtained by performing ultrasonic treatment with an oscillation frequency in the range of more than 20 kHz and not more than 60 kHz, a rated output in the range of more than 110 W and not more than 250 W, and for more than 120 minutes and up to 300 minutes.

[0053] The inventors of the present application have found through experiments that by performing ultrasonic treatment so as to satisfy such specific conditions, the fibrous carbon in the dispersion liquid can maintain some of the bundles without being completely disintegrated, and that by using a dispersion liquid containing fibrous carbon partially bundled in this way, a self-supporting positive electrode sheet having the above-mentioned BET specific surface area and pore volume can be obtained.

[0054] More preferably, the ultrasonic treatment is performed for 150 to 300 minutes with an oscillation frequency in the range of 30 to 50 kHz and a rated output in the range of 130 to 170 W. This allows the positive electrode sheet of the present invention to be obtained with good yield.

[0055] The ultrasonic treatment may be performed at room temperature, under cooling conditions (e.g., in an ice bath), or under heating conditions. Such ultrasonic treatment may be performed using an ultrasonic cleaning device. When an ultrasonic cleaning device is used, ultrasonic vibrations are not directly applied to the fibrous carbon in the dispersion liquid, so that the fibrous carbon can be partially bundled without being completely broken up.

[0056] Step S120: The dispersion liquid of the fibrous carbon obtained in step S110 is filtered on a filter.

[0057] Examples of filters include, but are not limited to, polytetrafluoromethylene (PTFE) membranes whose surfaces have been treated for hydrophilicity, polyvinylidene fluoride (PVDF) membranes whose surfaces have been treated for hydrophilicity, and glass fiber membranes.

[0058] The filtration method is not particularly limited, but is preferably suction filtration (also called reduced pressure filtration) or pressure filtration, which makes it easier to obtain a self-supporting sheet by entangling the fibrous carbon fibers with each other compared to natural filtration.

[0059] Step S130: The filter cake on the filter in step S120 is peeled off. This results in the above-mentioned positive electrode sheet. After peeling, the filter cake may be dried. This removes the dispersion medium. Drying may be performed after step S120, prior to peeling. Drying may be performed, for example, in a vacuum at a temperature range of 50 to 150° C. for 1 to 24 hours.

[0060] (Embodiment 2) In the second embodiment, an air battery using the air battery positive electrode sheet of the present invention will be described. FIG. 2 is a schematic cross-sectional view of an air battery according to an embodiment of the present invention.

[0061] The air battery 600 is an air battery generally referred to as a “coin cell type” battery, which has a laminate in which a negative electrode structure 610 (the structure will be described later) and a positive electrode structure 620 (the structure will be described later) are stacked with a separator 660 interposed therebetween, and a restraint 630 that restrains the laminate.

[0062] An insulating O-ring (not shown) is disposed between the restraint 630 and the metal mesh 680 to ensure insulation between the restraint 630 and the positive electrode structure 620.

[0063] As the name suggests, air batteries require a minimum supply of oxygen of 21%, which is the oxygen concentration in air, to reduce the effects of diffusion limitation. However, a higher concentration is preferable, and the best performance can be achieved by supplying pure oxygen.

[0064] The negative electrode structure 610 is composed of a current collector 635, a metal layer 640 arranged on the current collector 635, and columnar spacers 650 arranged on both ends of the current collector 635. A space 670 is provided between the metal layer 640 and a separator 660, and is filled with an electrolyte capable of conducting metal ions such as alkali metal ions and alkaline earth metal ions.

[0065] The metal layer 640 contains an alkali metal and / or an alkaline earth metal. Among these, a layer made of lithium metal is preferable. When the electrolytic solution can conduct lithium ions and the negative electrode structure 610 includes lithium metal, a lithium-air battery can be provided.

[0066] The positive electrode structure 620 includes a positive electrode sheet 690 that is mechanically and electrically in contact with a metal-containing mesh (metal mesh) 680 that is a current collector. In this case, the metal mesh 680 serves as a positive electrode substrate and also functions as a flow path through which air or oxygen passes. Since the positive electrode sheet 690 is the positive electrode sheet described in Embodiment 1, the description thereof is omitted. Also, in FIG. 2, it is described as including the metal mesh 680, but since the positive electrode sheet 690 has self-supporting properties, it may not have the metal mesh 680. This enables weight reduction.

[0067] A separator 660 that separates the negative electrode structure 610 and the positive electrode structure 620 is disposed therebetween.

[0068] Next, a method for manufacturing the air battery 600 will be described. First, the negative electrode structure 610 is prepared. On a disk-shaped current collector 635, a disk-shaped metal layer 640 made of lithium or the like that is concentric with the current collector 635 and has a smaller diameter than the current collector 635 is laminated, and a columnar spacer 650 is pressed onto the current collector 635 to obtain the negative electrode structure 610.

[0069] The spacer 650 is an insulator. The material may be a metal oxide, a metal nitride, a metal oxynitride, or the like. For example, Al2O3, Ta2O5, TiO2, ZnO, ZrO, SiO2, B2O3, P2O5, GeO2, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, Si3N4, AlN, and AlO x N 1-x (0 < x < 1), etc. Among these, Al2O3 and SiO2 are easily available and have excellent processability.

[0070] The spacer 650 may be made of a resin. Examples of the resin include polyolefin resin, polyester resin, polyimide resin, and polyether ether ketone (PEEK) resin. Examples of the polyolefin resin include polyethylene and polypropylene. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polytributylene terephthalate (PTT). These resins are easily available and have excellent processability.

[0071] Next, a separator 660 is prepared and pressed onto the spacer 650 . The separator 660 is a porous insulator that allows alkali metal ions and / or alkaline earth metal ions to pass through it. The separator 660 is any inorganic material (including metallic materials) or organic material that is non-reactive with the metal layer 640 and the electrolyte.

[0072] The material of the separator 660 may be a resin such as polyethylene, polypropylene, or polyolefin, glass, etc. The separator 660 may be a nonwoven fabric. A space 670 is provided between the metal layer 640 (lithium metal), the spacer 650 and the separator 660 .

[0073] Thereafter, the electrolyte is filled into separator 660. At this time, space 670 is also filled with the electrolyte.

[0074] The electrolyte may be any aqueous or non-aqueous electrolyte containing an alkali metal salt and / or an alkaline earth metal salt. When the aqueous electrolyte contains a lithium salt, the lithium salt may be, for example, LiOH, LiCl, LiNO3, or Li2SO4. The solvent may be water or a water-soluble solvent.

[0075] When the non-aqueous electrolyte (nonaqueous electrolyte) contains a lithium salt, examples of the lithium salt that can be used include LiNO3, LiPF6, LiBF4, LiSbF6, LiSiF6, LiAsF6, LiN(SO2C2F5)2, Li(FSO2)2N, LiCF3SO3(LiTfO), Li(CF3SO2)2N(LiTFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, and LiB(C2O4)2.

[0076] In the non-aqueous electrolyte, the non-aqueous solvent may be glymes (monoglyme, diglyme, triglyme, tetraglyme), methyl butyl ether, diethyl ether, ethyl butyl ether, dibutyl ether, polyethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, cyclohexanone, dioxane, dimethoxyethane, 2-methyltetrahydrofuran, 2,2-dimethyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, methyl formate, ethyl formate, dimethyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether ... Examples of the alkyl esters include ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, polyethylene carbonate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, acetonitrile, benzonitrile, nitromethane, nitrobenzene, triethylamine, triphenylamine, tetraethylene glycol diamine, dimethylformamide, diethylformamide, N-methylpyrrolidone, dimethylsulfone, tetramethylene sulfone, triethylphosphine oxide, 1,3-dioxolane, and sulfolane.

[0077] Thereafter, a positive electrode structure 620 is prepared in which a metal mesh is disposed on a positive electrode sheet 690 . As the metal mesh 680, for example, a mesh having at least one metal selected from the group consisting of copper (Cu), tungsten (W), aluminum (Al), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt), and palladium (Pd) can be used. That is, examples of the mesh include a simple metal selected from this group, an alloy containing a metal selected from this group, and a compound of a metal selected from this group with carbon (C), nitrogen (N), or the like. The mesh can have a thickness of 0.2 mm and a mesh size of 1 mm, for example.

[0078] Thereafter, the positive electrode structure 620 is attached to the negative electrode structure 610 filled with the electrolyte via a separator 660, and the electrodes are restrained by a restraining device 630 to obtain an air battery 600. Here, the mounting is preferably performed in dry air, for example, in dry air with a dew point temperature of −50° C. or lower. Through the above steps, a coin cell type air battery 600 is manufactured.

[0079] Although the air battery 600 has a positive electrode sheet 690 and a metal mesh 680 as the positive electrode structure 620, the air battery of the present invention is not limited to the above and may have only the positive electrode sheet 690 as the positive electrode structure 620.

[0080] The manufactured air battery 600 is an excellent air battery that has a large capacity despite its small size and light weight, since the positive electrode structure 620 using the positive electrode sheet 690 has excellent air or oxygen permeability, can take in a large amount of oxygen, has high ion transport efficiency, and has a large reaction field.

[0081] Next, as another embodiment of the air battery, a stacked metal battery (air battery) will be described with reference to the drawings.

[0082] FIG. 3 is a schematic cross-sectional view of an air battery, which is a laminated metal battery, which is another embodiment of the air battery of the present invention.

[0083] The air battery 500 of the present invention has a laminated structure in which a positive electrode structure 510 and a negative electrode structure 100 are laminated via a separator 540. The number of laminated pairs may be one or more pairs, with one positive electrode structure 510 and one negative electrode structure 100 being regarded as one pair, and there is no particular upper limit to the number of pairs.

[0084] Here, the negative electrode structure 100 is composed of a pair of negative electrode structures and a negative electrode current collector electrode 520 sandwiched between them. The negative electrode structure is the same as the negative electrode structure 610 of the air battery 600.

[0085] On the other hand, the positive electrode structure 510 is composed of a pair of laminates each including a positive electrode sheet 550 and a gas diffusion layer 560, and a positive electrode collector electrode 525 sandwiched between the laminates. The gas diffusion layer 560 and the positive electrode sheet 550 are arranged in this order from the positive electrode collector electrode 525 side. The positive electrode sheet 550 is the positive electrode described in the first embodiment, and therefore a description thereof will be omitted.

[0086] Since the positive collector electrode 525 also functions as a flow path for air or oxygen, the air battery 500 can have a larger capacity with a simpler structure.

[0087] For example, metals such as copper (Cu), tungsten (W), aluminum (Al), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt), and palladium (Pd), as well as alloys and compounds of these (for example, compounds with carbon and / or nitrogen) can be used for the negative collector electrode 520 and the positive collector electrode 525. The air battery 500 may be housed in a container (not shown).

[0088] The positive electrode structure 510 of the air battery 500 includes a gas diffusion layer 560 between the positive electrode sheet 550 and the positive electrode collector electrode 525, and air, oxygen, and other gases pass through this gas diffusion layer to travel between the outside of the battery and the positive electrode sheet 550. The gas diffusion layer also functions as a path for electrons to travel between the positive electrode sheet 550 and the positive electrode collector electrode 525. Since the gas diffusion layer functions as a path for the gases, it is necessary for the gas diffusion layer to have holes for air permeability and to have electronic conductivity. For example, Toray's carbon paper TGP-H and Kureha's KREKA E704 can be used as the gas diffusion layer.

[0089] In addition to the air batteries described above, the positive electrode sheet of the present invention can also be used in other metal batteries such as sodium-air batteries, zinc-air batteries, iron-air batteries, aluminum-air batteries, and magnesium-air batteries.

[0090] The present invention will now be described in detail with reference to specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES

[0091] [Raw materials] In the production of the sheets of Examples 1 to 10 described later, carbon nanotubes shown in Table 1 were used as the raw material fibrous carbon. Single-walled CNT1 is a single-walled carbon nanotube (MEIJO eDIPS (EC2.0)) manufactured by Meijo Nano Carbon Co., Ltd., multi-walled CNT2 is a multi-walled carbon nanotube (DL) manufactured by Taiyo Nippon Sanso Co., Ltd., multi-walled CNT2 is a multi-walled carbon nanotube (FloTube9000) manufactured by CNano Technology Ltd., and single-walled CNT1 is a single-walled carbon nanotube (ZEONANO (registered trademark) SG101) manufactured by Zeon Technology Co., Ltd.

[0092] [Table 1]

[0093] [Characteristics evaluation] The properties of the sheets of Examples 1 to 10 described below were evaluated as follows. (1) Weight The sheets were each punched out to a diameter (φ) of 16 mm, and their weights (mg) were measured. The weight per unit area of ​​the punched sheets was calculated as the basis weight (mg / cm 2 ) was decided.

[0094] (2) Sheet density (apparent density) Sheet density (ρ sheet ) was calculated by dividing the basis weight by the sheet thickness. (3) Porosity The porosity is calculated by setting the true density of the raw material of carbon nanotubes to 1.3 g / cm 3 The calculation was made according to the following formula: Porosity(%)={1-(ρ sheet / 1.3)}×100

[0095] (4) Raman R value The Raman spectrum was obtained using a Nanophoton Corporation Raman spectrometer Touch-VIS-NIR with a 10x objective lens, an excitation wavelength of 532 nm, and an irradiation laser power of 1 mW. The peak intensity due to crystalline carbon was defined as G, and the peak intensity due to turbostratic carbon was defined as D, and the value of D / G was used.

[0096] (5) BET method specific surface area The adsorption isotherm was obtained by nitrogen adsorption using 3Flex (Micromeritics Instrument Corp.) according to the BET method.

[0097] (6) Pore volume occupied by pores with diameters of 2 to 1,000 nm The adsorption isotherm was obtained by nitrogen adsorption using 3Flex (Micromeritics Instrument Corp.) and was calculated using the BJH method.

[0098] (7) Pore volume occupied by pores with diameters of 0.1 to 10 μm The pore volume in the pore diameter range of 10 to 200,000 nm (0.01 to 200 μm) was measured by mercury intrusion method using AutoPoreIV (Micromeritics Instrument Corp.), and the value of the pore volume in the pore diameter range of 0.1 to 10 μm was used.

[0099] (8) Electrolyte penetration time Sheet (area 2cm 2 The time from when 10 μL of the electrolyte was dropped onto a sheet (50 to 150 μm thick) using a micropipette until the electrolyte was absorbed into the sheet and disappeared from the sheet surface was measured. The electrolyte used was a 1M solution of LiTFS (lithium trifluoromethanesulfonate) in tetraethylene glycol dimethyl ether.

[0100] [Battery characteristic evaluation] The discharge capacity and cycle characteristics were evaluated as the battery characteristics of the sheet of the example described later. (1) Discharge capacity (discharge rate characteristics) The sheet was punched out to a diameter (φ) of 16 mm, and vacuum dried at 100°C for 12 hours or more to obtain a positive electrode sheet. A lithium metal foil (diameter (φ) 16 mm, thickness 0.2 mm) was used as the negative electrode structure, and glass fiber paper (Whatman (registered trademark), GF / A) was used as the separator. The lithium metal foil / glass fiber paper / positive electrode sheet were stacked in this order and mounted in a coin cell case (CR2032 type). Next, an electrolyte (1M-tetraethylene glycol dimethyl ether solution of LiTFSI (lithium bistrifluoromethanesulfonimide)) was permeated into the negative electrode structure to produce a lithium-air battery cell.

[0101] Using a battery charge / discharge system (Hokuto Denko, HJ1001SD8), the battery was charged at room temperature (25°C) under a pure oxygen flow environment at a constant current (0.4 mA / cm 2 , 1.0mA / cm 2 , 2.0mA / cm 2 ) The discharge capacity of the lithium-air battery cell was measured at 2 V cutoff under these conditions.

[0102] (2) Cycle characteristics A lithium-air battery cell was produced in the same manner, except that a tetraethylene glycol dimethyl ether solution containing 0.5 M LiTFSI, 0.5 M LiNO3 (lithium nitrate) and 0.2 M LiBr (lithium bromide) was used instead of LITFSI as the electrolyte.

[0103] Using a battery charge / discharge system (Hokuto Denko, HJ1001SD8), the battery was charged at room temperature under a pure oxygen flow environment at a constant current (0.4 mA / cm 2 ) conditions, the lithium-air battery cell was repeatedly discharged and charged for 10 hours with a cutoff voltage of 2-4.5 V, and the number of charge-discharge cycles was determined by subtracting 1 from the number of cycles at which the 2 V cutoff voltage was first reached.

[0104] [Example 1 to Example 3] In Examples 1 to 3, the positive electrode sheets of the present invention were produced using the single-walled CNT2 carbon nanotubes shown in Table 1 under the production conditions shown in Table 2. The following will be explained in detail.

[0105] The sheets of Examples 1 to 3 were obtained as follows. Single-walled CNT2 (75 mg) was dispersed in a container containing ultrapure water (150 g) and ultrasonically treated using an ultrasonic cleaner (MCD-6, manufactured by AS ONE Corporation) under the ultrasonic treatment conditions shown in Table 2 to obtain a dispersion (Step S110 in FIG. 1). The obtained dispersion was filtered onto a hydrophilic polytetrafluoroethylene (PTFE, Omnipore® JAWP, manufactured by Merck Ltd., pore size 1 μm) filter (Step S120 in FIG. 1). The filtration area was 2.5 cm 2 The amount of the filtered dispersion was 16 mL, and was suction filtered using a diaphragm vacuum pump (KNF, N820.3FT.18). The obtained residue was peeled off from the filter (step S130 in FIG. 1) and dried. The drying conditions were 60° C. in a vacuum for 12 hours.

[0106] The sheets of Examples 1 to 3 were visually observed to determine whether they were self-supporting films, and their details were observed using a scanning electron microscope (SEM, manufactured by JEOL Ltd., JSM-7800F). The above-mentioned property evaluations were carried out for the sheets of Examples 1 to 3. These results are shown in Figs. 4 and 5 and Table 3. The above-mentioned battery characteristic evaluations were carried out using the sheets of Examples 1 to 3 as the positive electrode. The results are shown in Tables 4 and 5.

[0107] [Example 4] In Example 4, a positive electrode sheet was produced using single-walled CNT2 carbon nanotubes shown in Table 1 under the production conditions shown in Table 2. Example 4 was carried out in the same manner as Examples 1 to 3 except that the ultrasonic treatment time was 120 minutes, and therefore a description thereof will be omitted.

[0108] In addition, when the sheet of Example 4 was visually observed, it was found not to be able to stand on its own, and therefore no further tests were carried out.

[0109] [Example 5] In Example 5, a positive electrode sheet was produced under the production conditions shown in Table 2 using single-walled CNT2 carbon nanotubes shown in Table 1.

[0110] Example 5 was the same as Examples 1 to 3, except that special-grade isopropanol was used as the dispersion medium, and ultrasonic treatment was performed using an ultrasonic homogenizer (Branson, 450D) under the ultrasonic treatment conditions shown in Table 2 to obtain a dispersion. As in Examples 1 to 3, the sheet of Example 5 was visually observed and SEM observed to determine whether it was a free-standing film, and its properties were evaluated. The results are shown in FIG. 6 and Table 3.

[0111] [Example 6] In Example 6, a positive electrode sheet was produced using carbon nanotubes of single-walled CNT1 shown in Table 1 under the production conditions shown in Table 2. Example 6 was the same as Example 5 except that single-walled CNT1 was used as the raw CNT, and therefore a description thereof will be omitted.

[0112] As in Examples 1 to 3, the sheet of Example 6 was visually observed and SEM observed to determine whether it was a self-supporting film, and its properties were evaluated. The results are shown in FIG. 7 and Table 3. As in Examples 1 to 3, the sheet of Example 6 was evaluated for its battery properties. The results are shown in Tables 4 and 5.

[0113] [Example 7] In Example 7, a positive electrode sheet was produced under the production conditions shown in Table 2 using the multi-walled CNT1 carbon nanotubes shown in Table 1.

[0114] In Example 7, multi-walled CNT1 (113 mg) was used with 226 g of isopropanol (special grade) as a dispersion medium, and ultrasonic treatment was performed using a BRONSON homogenizer SFX550 under the conditions shown in Table 2 to obtain a dispersion. The obtained dispersion was filtered onto a 90 mmφ hydrophilic polytetrafluoroethylene filter (PTFE, manufactured by Merck Ltd., Omnipore® JAWP, pore size 1 μm). The filtration area was 43 cm 2 The amount of the filtered dispersion was 280 mL, and the dispersion was filtered by pressurizing with compressed nitrogen at 0.2 MPa. Next, the carbon nanotubes remaining on the filter were peeled off from the filter, dried in a vacuum at 50°C for 3 hours, and further dried in a vacuum at 110°C for 16 hours to completely remove isopropanol, thereby obtaining a positive electrode sheet of Example 7. As in Examples 1 to 3, the sheet of Example 7 was visually observed and SEM observed to determine whether it was a self-supporting film, and properties were evaluated. The results are shown in FIG. 8 and Table 3. As in Examples 1 to 3, the sheet of Example 7 was evaluated for battery properties. The results are shown in Tables 4 and 5.

[0115] [Example 8] In Example 8, a positive electrode sheet was produced under the production conditions shown in Table 2 using the carbon nanotubes of multi-walled CNT2 shown in Table 1. Example 8 is the same procedure as Example 5 except that multi-walled CNT2 was used as the raw CNT, so a description is omitted. As in Examples 1 to 3, the sheet of Example 7 was visually observed and SEM observed to determine whether it was a free-standing film, and its properties were evaluated. The results are shown in Table 3.

[0116] [Example 9] In Example 9, a positive electrode sheet was manufactured under the manufacturing conditions shown in Table 2 using a mixture of single-walled CNT1 and multi-walled CNT2 shown in Table 1. Example 9 was manufactured using the same procedure as Example 5, except that a mixture of single-walled CNT1 (30 mg) and multi-walled CNT2 (45 mg) was used as the raw CNT, so a description will be omitted. As in Examples 1 to 3, the sheet of Example 9 was visually observed and SEM observed to determine whether it was a free-standing film, and its properties were evaluated. The results are shown in FIG. 9 and Table 3.

[0117] [Example 10] In Example 10, a positive electrode sheet was manufactured under the manufacturing conditions shown in Table 2 using a mixture of single-walled CNT1 and multi-walled CNT2 shown in Table 1. Example 10 was performed in the same manner as Example 9, except that a mixture of single-walled CNT1 (7.5 mg) and multi-walled CNT2 (67.5 mg) was used as the raw CNT, so a description thereof will be omitted. As in Examples 1 to 3, the sheet of Example 10 was visually observed and SEM observed to determine whether it was a free-standing film, and its properties were evaluated. The results are shown in Table 3.

[0118] For simplicity, the production conditions are shown in Table 2, and the results are summarized and explained.

[0119] [Table 2]

[0120] The results of the property evaluation of the sheets of Examples 1 to 10 are shown in Table 3.

[0121] [Table 3]

[0122] According to Examples 1 to 10, when the raw material was multi-walled CNT2 alone (Example 8) or when the raw material contained more than 60 mass% multi-walled CNT2 (Example 10), a free-standing sheet was not obtained regardless of the ultrasonic treatment conditions, but when other raw materials were used, a free-standing sheet was obtained by controlling the ultrasonic treatment conditions. Also, when single-walled CNT2 was used as the raw material and the ultrasonic treatment time was 120 minutes (Example 4), a free-standing sheet was not obtained.

[0123] Thus, according to Examples 1 to 4, 400 to 1300 m 2 / g and 8.0 to 15.0 cm 3 It was found that a self-supporting sheet can be obtained by using a dispersion obtained by using as a raw material fibrous carbon having a pore volume of pores with a diameter of 2 to 1000 nm that satisfies the range of 1 / g, and performing ultrasonic treatment at a temperature in the range of more than 20 kH and not more than 60 kH and a rated output in the range of more than 110 W and not more than 250 W for more than 120 minutes and 300 minutes.

[0124] According to Examples 1 to 3, it was found that sheets having both a large pore volume and a large specific surface area can be obtained by using water, which has poor dispersibility for carbon nanotubes, as a dispersion medium and dispersing the carbon nanotubes under specific ultrasonic treatment conditions. In detail, the sheets of Examples 1 to 3 have a pore volume of 2.0 to 10.0 cm for pores with diameters of 0.1 to 10 μm. 3 / g range, and the BET specific surface area is 400 to 1300 m 2 It was found that the range of / g was satisfied.

[0125] The sheets of Examples 1 to 3 further have a density of 0.05 to 0.2 g / cm 3 Furthermore, the sheets of Examples 1 to 3 had a low sheet density in the range of 0.5 to 2.0 cm3 for pores having a diameter of 2 to 1000 nm, and were flexible. 3 / g range. Furthermore, the sheets of Examples 1 to 3 had a high porosity in the range of 80 to 95%.

[0126] FIG. 4 shows an SEM image of the sheet of Example 1. FIG. 5 shows an SEM image of the sheet of Example 3. FIG. 6 shows an SEM image of the sheet of Example 5. FIG. 7 shows an SEM image of the sheet of Example 6. FIG. 8 shows an SEM image of the sheet of Example 7. FIG. 9 shows an SEM image of the sheet of Example 9.

[0127] According to Figs. 4 to 9, all the sheets were in the form of a nonwoven sheet made of carbon nanotubes. In particular, according to Figs. 4 and 5, it was found that the sheets of Example 1 and Example 3 were made of thick carbon nanotubes with a width in the range of 0.1 to 10 μm, and some of the carbon nanotubes were bundled. Although not shown, the sheet of Example 2 also showed a similar form. The sheets of Example 1 to Example 3 had large gaps between the bundles, and had a structure that facilitated oxygen diffusion. On the other hand, according to Figs. 6 to 9, the sheets of Example 5 to Example 7 and Example 9 showed some bundles of carbon nanotubes, but the width was narrower than 0.1 μm, and the gaps were also small.

[0128] It should be noted that the sheet in Example 5 in Fig. 6 uses the same raw material, single-walled CNT2, as in Examples 1 to 3, but the bundles are finely crushed and have a dense structure. It was found that such differences in the state of the sheet are largely dependent on the conditions of the ultrasonic treatment when obtaining the dispersion.

[0129] Referring again to Table 3 and noting the electrolyte permeation time, it was found that the sheets of Examples 1 to 3 completely absorbed the electrolyte in a few seconds to several tens of seconds and had high electrolyte permeability. This is because the sheets of Examples 1 to 3 have a D / G in the range of 0.3 to 0.6 and low crystallinity.

[0130] From the above, it was found that by using fibrous carbon having a specific BET specific surface area and pore volume as a raw material and filtering a dispersion liquid dispersed under specific ultrasonic treatment conditions, the pore volume of pores having a diameter of 0.1 to 10 μm can be increased to 2.0 to 10.0 cm. 3 / g range, and the BET specific surface area is 400 to 1300 m2 It was shown that a sheet made of fibrous carbon satisfying the range of 0.1 g / g could be obtained.

[0131] Next, Tables 4 and 5 show the results of discharge capacity and number of charge / discharge cycles as an evaluation of battery characteristics when the sheets of Examples 1 to 3, 6, 7, and 9 were used as positive electrodes, respectively.

[0132] [Table 4]

[0133] According to Table 4, the batteries using the sheets of Examples 1 to 3, 6 and 9 had a current of 0.4 mA cm -2 At a low rate of 4000mAhg -1 The discharge capacity of the battery using the sheet of Example 7 was 1700 mAhg even at a low rate. -1 This is believed to be because the BET specific surface area of ​​the sheet of Example 7 is small, resulting in a shortage of electrochemically active surfaces and making it impossible to keep up even at a low rate.

[0134] The discharge capacity of the sheets in Examples 1 to 3 is 1.0 mA cm -2 The large value was maintained even when the rate was increased to 2.0 mAcm. -2 Even when the discharge current was increased to 1.0 mA cm, the sheets of Examples 1 to 3 maintained a relatively high discharge capacity. -2 The discharge capacity of the sheets of Examples 7 and 9 was 1.0 mA cm -2 The charge was dramatically reduced at the rate above 2.0 mA cm. Therefore, for the batteries using the sheets of Examples 6 to 7, the charge was further increased to 2.0 mA cm. -2 The discharge capacity was not measured when the discharge current was increased to 100 mA.

[0135] As shown in Table 3, the sheets of Examples 1 to 3 have a low sheet density, a large pore volume, and a BET specific surface area, so that oxygen diffusion inside the sheet is easy and the sheet has many electrochemically active surfaces. As a result, it was found that the sheets of Examples 1 to 3 function as positive electrode sheets for air batteries with excellent rate characteristics (discharge characteristics).

[0136] [Table 5]

[0137] According to Table 5, the number of charge / discharge cycles of the air batteries using the sheets of Examples 1 to 3, which have excellent rate characteristics in Table 4, as the positive electrode was greater than those of Examples 6, 7, and 9, and both the discharge voltage and the charge voltage tended to be stable.

[0138] As shown in Table 3, the sheets of Examples 1 to 3 have a low sheet density, a large pore volume, a BET specific surface area, and high electrolyte permeability, and therefore tend to retain electrolyte inside the sheet during charge / discharge cycles. As a result, it was found that the sheets of Examples 1 to 3 function as positive electrode sheets for air batteries with excellent rate characteristics and cycle characteristics. [Industrial Applicability]

[0139] The positive electrode sheet for an air battery of the present invention is made of fibrous carbon having a specific pore volume and BET specific surface area, and by using this for the positive electrode of an air battery, it is possible to provide an air battery with high battery capacity and high load characteristics due to high air or oxygen diffusivity, high ion transport efficiency, and a wide reaction field. In addition, the positive electrode sheet made of fibrous carbon has the self-supporting property that can be used alone as a positive electrode without using a current collector such as a metal mesh, and therefore it is possible to provide an air battery that is small, lightweight, and suitable for large capacity. For this reason, it is expected that the present invention will be preferably used for air batteries, the demand of which is expected to expand significantly in the future. [Explanation of symbols]

[0140] 100: Negative electrode structure 500: Air battery 510: Positive electrode structure 520: Negative electrode current collector 525: Positive current collector electrode 540: Separator 550: Positive electrode sheet 560: Gas diffusion layer 600: Air battery 610: Negative electrode structure 620: Positive electrode structure 630: Restraints 635: Current collector 640: Metal layer 650: Spacer 660: Separator 670: Space 680: Metal mesh 690: Positive electrode sheet

Claims

1. It is made of fibrous carbon, The pore volume of pores with a diameter of 0.1 to 10 μm is 2.0 to 10.0 cm 3 / g range, BET specific surface area: 400 to 1300 m 2 / g range, The pore volume of pores having a diameter of 2 to 1000 nm is in the range of 0.5 to 2.0 cm 3 / g. Positive electrode sheet for air batteries.

2. The apparent density is 0.05 to 0.2 g / cm 3 The positive electrode sheet according to claim 1 , which satisfies the above range.

3. The apparent density is 0.07 to 0.19 g / cm 3 The positive electrode sheet according to claim 2 , which satisfies the above range.

4. The pore volume of the pores having a diameter of 0.1 to 10 μm is 2.3 to 8.0 cm 3 The positive electrode sheet according to any one of claims 1 to 3, wherein the positive electrode sheet satisfies the range of / g.

5. The pore volume of the pores having a diameter of 0.1 to 10 μm is 2.5 to 5.0 cm 3 The positive electrode sheet according to claim 4 , wherein the positive electrode sheet satisfies the range of / g.

6. The BET specific surface area is 500 to 1200 m 2 The positive electrode sheet according to any one of claims 1 to 5, wherein the positive electrode sheet satisfies the range of / g.

7. The BET specific surface area is 550 to 1000 m 2 The positive electrode sheet according to claim 6 , wherein the positive electrode sheet satisfies the range of / g.

8. The positive electrode sheet according to any one of claims 1 to 7, wherein the fibrous carbon is selected from the group consisting of carbon nanotubes, carbon nanohorns, and carbon nanofibers.

9. The positive electrode sheet according to any one of claims 1 to 8, wherein a portion of the fibrous carbon is in a bundle shape.

10. The positive electrode sheet according to any one of claims 1 to 9, wherein the intensity ratio D / G of the peak intensity D derived from the turbostratic carbon to the peak intensity G derived from the crystalline carbon obtained by Raman spectroscopy is in the range of 0.1 to 1.

0.

11. The positive electrode sheet according to claim 10, wherein the intensity ratio D / G is in the range of 0.2 to 0.

8.

12. The pore volume of the pores having a diameter of 2 to 1000 nm is 0.7 to 1.0 cm 3 The positive electrode sheet according to any one of claims 1 to 11, wherein the positive electrode sheet satisfies the range of / g.

13. The positive electrode sheet according to any one of claims 1 to 12, wherein the porosity is in the range of 80 to 95%.

14. The positive electrode sheet according to any one of claims 1 to 13, wherein the electrolyte permeation time when a 10 μL droplet is permeated into the positive electrode sheet is in the range of more than 0 minutes and not more than 6 minutes.

15. The positive electrode sheet according to claim 14 , wherein the electrolyte penetration time is in the range of more than 0 minutes and not more than 2 minutes.

16. The positive electrode sheet according to any one of claims 1 to 15, having a thickness in the range of 50 to 400 µm.

17. The basis weight is 2 to 3.5 mg / cm 2 The positive electrode sheet according to any one of claims 1 to 16, which satisfies the above range.

18. A battery comprising a positive electrode, a negative electrode, and an electrolyte capable of conducting metal ions between the positive electrode and the negative electrode, An air battery, wherein the positive electrode comprises the positive electrode sheet according to any one of claims 1 to 17.

19. The negative electrode comprises a lithium metal layer; 19. The air battery of claim 18, wherein the metal ions are lithium ions.

Citation Information

Patent Citations

  • Carbon nanotube and dispersion liquid thereof, and self-supporting film and composite material

    JP2015105208A

  • Porous carbon structure, manufacturing method therefor, positive electrode material using same, and battery using same

    WO2020235638A1